Hospital Brand Image, Service Quality, and Patient Satisfaction in Pandemic Situation - Tjokorda Gde Raka Sukawati (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
The aim of this research was to analyze the effect of hospital brand image, service quality, and patient satisfaction on hospital service users in Denpasar, Bali. This study was conducted during the current pandemic. This study aimed at testing the important mediation role of service quality in relation to hospital brand image on patient satisfaction. This study took the research samples of 81 respondents who used medical services at hospitals in Denpasar. The simple random sampling technique was used to collect the data. The hypothesis test results show that hospital brand image positively, significantly influences patient satisfaction. Hospital brand image positively, significantly influences service quality. Service quality positively, significantly influences patient satisfaction.